2014
DOI: 10.4236/eng.2014.62009
|View full text |Cite
|
Sign up to set email alerts
|

Gynecological Surgery and the Robot

Abstract: As the only robotic device with FDA approval for gynecological surgery, the da Vinci ® Surgical System dominates robot-assisted surgery in the field. Benefits to the Surgeon include decreased risk of neck and back injury secondary to improved ergonomics. However, patients benefit greatly due to decreased length of stay, decreased blood loss and analgesic requirements. Unfortunately the initial economic impact of purchasing and maintaining a robot is great but must be balanced with the potential savings from re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 114 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…The first documented usage of Da Vinci during a gynaecological operation in our country was in 2010 [11], and in our hospital in 2015. Robotic surgery which is used for various gynaecological indications is most frequently applied in benign processes such as uterine fibroids, uterine bleedings resistant to treatment, endometrial pathologies, ovarian cysts, endometrioma, tubal pathologies, re-anastomosis, and some gynecologic oncology cases [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The first documented usage of Da Vinci during a gynaecological operation in our country was in 2010 [11], and in our hospital in 2015. Robotic surgery which is used for various gynaecological indications is most frequently applied in benign processes such as uterine fibroids, uterine bleedings resistant to treatment, endometrial pathologies, ovarian cysts, endometrioma, tubal pathologies, re-anastomosis, and some gynecologic oncology cases [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that participation in a minimum of 50 cases should be sufficient to overcome the learning curve . The learning curves for different robotic gynaecological surgeries vary from 20 cases for hysterectomy and pelvic lymphadenectomy for endometrial cancer, to 50 cases for benign hysterectomies and 10 cases for sacrocolpopexy . As a comparison, traditional laparoscopic sacrocolpopexy was shown to have a learning curve between 18–24 cases …”
Section: Training In Robotic Surgerymentioning
confidence: 99%
“…Dual console training can also facilitate training and collaboration between the mentor and trainee. Finally, live surgery under the guidance of a proctor for the first few robotic courses allows direct supervision and familiarisation with the new technique . All cases performed should be reviewed for outcomes and complications …”
Section: Training In Robotic Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…In 2000, the FDA approved the da Vinci Surgical System, created by Intuitive Surgical, for minimally invasive surgery. However, it took five more years for the FDA to approve the surgical system's use in gynecologic procedures (1). The da Vinci Surgical System quickly grew in demand due to its unique advantages such as improved visualization, ergonomics, and a variety of surgical tools with stereotactic freedom matching an individual's hand-eye coordination (1).…”
mentioning
confidence: 99%